2019
DOI: 10.3389/fendo.2019.00482
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in Thyroid Disorders

Abstract: Arterial hypertension represents a major global health concern; more than one fourth of the population is affected by high blood pressure. Albeit the underlying cause of the disease remains unclear in the vast majority of the cases, ~10% are of secondary origin. Endocrine disorders are common illnesses and some of them may lead to elevated blood pressure, among which thyroid diseases are of high prevalence and often overlooked, especially in mild cases. Overt and subclinical hyper- and hypothyroidism can both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(122 citation statements)
references
References 125 publications
(158 reference statements)
3
88
0
12
Order By: Relevance
“…Moreover, the risk of recurrence after discontinuation of a full course of antithyroid therapy is 50-70 % [14]. Along with the statement that most cardiac disorders in TT, including AH, return to normal when the euthyroid state is restored, it is the lack of restoration of myocardial structure and function can be considered as a cause of increased mortality from cardiovascular causes by 1.2 times and cerebrovascular complications 1.4 times in TT compared with the general population [4,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the risk of recurrence after discontinuation of a full course of antithyroid therapy is 50-70 % [14]. Along with the statement that most cardiac disorders in TT, including AH, return to normal when the euthyroid state is restored, it is the lack of restoration of myocardial structure and function can be considered as a cause of increased mortality from cardiovascular causes by 1.2 times and cerebrovascular complications 1.4 times in TT compared with the general population [4,7].…”
Section: Discussionmentioning
confidence: 99%
“…Yildiz C. and et al (2019) found in patients with thyrotoxicosis (TT) a significant increase in systolic blood pressure (SBP), heart rate (HR) and central SBP, which is an independent risk factor for cardiovascular complications, which is more accurate than the level of peripheral blood pressure (BP) displays after loading of the left ventricle (LV) and closely correlates with the left ventricular myocardial mass index (LVMMI) n patients with AH [2,3]. In patients with TT, the connection of arterial stiffness with the level of thyroid hormones has been proven [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid function has been clinically linked to time to draw a clock as a form of cognitive measurement (41). Other trait associations identified in PhenomeXcan with TPO include "Single major depression episode" (p-value=2.48x 10 -4 , locus RCP < 0.1) and "Treatment with doxazosin" (a medication used in the UK for hypertension) (p-value=8.80 x 10 -4 , locus RCP=0.12), both of which have demonstrated clinical association with thyroid abnormalities (42,43). To our knowledge, none of these traits have been deeply investigated with TPO previously, highlighting how PhenomeXcan may be useful in expanding gene-trait association studies and functional studies through consideration of independent traits associated with a given gene.…”
Section: Identifying Novel and Underreported Gene-trait Associationsmentioning
confidence: 99%
“…The prevalence of thyrotoxicosis is 10-fold higher in women. Elevated diastolic blood pressure is present in ~30% of patients with overt hypothyroidism and heart failure develops in 6-16% of patients with hyperthyroidism [77]. There is a high (>20%) prevalence of hypothyroidism in patients with T2DM, hypertension, and patients having both [189].Hypothyroidism can directly cause obstructive sleep apnea (OSA) [190,191], Bruyneel et.al, 2019 reported 16% of OSA patients had a thyroid problem and 8% of these were newly diagnosed with subclinical hypothyroidism (SCH) [192], over 50% of the patients studied did not receive any treatment, found in a recent Egyptian study [193].…”
Section: Thyroid Disordersmentioning
confidence: 99%